Hysteresis performance study of SRUHSC frame based on rod segment fiber model - Duan, Qing-Yu; Wang, Qiang; Yang, Chun-Xiao (Frontiers in Built Environment, 2025)
IntroductionWith the large-scale construction of high-rise and super high-rise buildings, structures combining ultra-high strength concrete and steel sections are increasingly applied in practical engineering.MethodsAccurately predicting the elastoplastic behavior of frame structures containing steel-reinforced ultra-high performance concrete (SRUHPC) components is crucial for assessing the seismic safety and studying the collapse performance of buildings with such components. To expand the application range of the SRC-SFM based on DEM (Discrete Element Method), this paper introduces a UHPC constitutive model based on SRC-SFM, constructing an SFM suitable for SRUHPC components. On this basis, it also achieves the establishment of a comprehensive SRHSC model. The SRUHPC SFM model is further validated through comparisons with the hysteretic performance of SRUHPC components and plane frames of different stories.ResultsComprehensive indicators including hysteretic curves, stress-strain relationships of various fibers at the column base, energy dissipation curves, and stiffness degradation curves prove that SRUHPC-SFM can be used to simulate the hysteretic performance of SRUHPC components and SRUHPC plane frames.DiscussionThis extends the application of DEM in studying the non-linear mechanical properties of structures containing SRUHPC components before collapse, laying a solid foundation for accurate simulation of the entire collapse process of structures containing SRUHPC components using DEM.